Tailoring Nutritional Advice for Mexicans Based on Prevalence Profiles of Diet-Related Adaptive Gene Polymorphisms - Ojeda-Granados, Claudia (J Pers Med, 2017)
Diet-related adaptive gene (DRAG) polymorphisms identified in specific populations are associated with chronic disorders in carriers of the adaptive alleles due to changes in dietary and lifestyle patterns in recent times. Mexico’s population is comprised of Amerindians (AM) and Mestizos who have variable AM, European (EUR) and African genetic ancestry and an increased risk of nutrition-related chronic diseases. Nutritional advice based on the Mexican genome and the traditional food culture is needed to develop preventive and therapeutic strategies. Therefore, we aimed to provide a prevalence profile of several DRAG polymorphisms in the Mexican population, including Central West (CW) Mexico subpopulations. Geographic heat maps were built using ArcGIS10 (Esri, Redlands, CA, USA) software, based on the published data of the MTHFR C677T (rs1801133), ABCA1 Arg230Cys (rs9282541), APOE T388C (rs429358)/C526T (rs7412), LCT C-13910T (rs4988235) polymorphisms and AMY1 copy number variation (CNV). Also, new data obtained by allelic discrimination-real-time polymerase chain reaction (RT-PCR) assays for the MTHFR, ABCA1, and APOE polymorphisms as well as the AMY1 CNV in the CW Mexico subpopulations with different proportions of AM and EUR ancestry were included. In the CW region, the highest frequency of the MTHFR 677T, ABCA1 230C and APOE ε4 adaptive alleles was observed in the AM groups, followed by Mestizos with intermediate AM ancestry. The LCT-13910T allele frequency was highest in Mestizos-EUR but extremely low in AM, while the AMY1 diploid copy number was 6.82 ± 3.3 copies. Overall, the heat maps showed a heterogeneous distribution of the DRAG polymorphisms, in which the AM groups revealed the highest frequencies of the adaptive alleles followed by Mestizos. Given these genetic differences, genome-based nutritional advice should be tailored in a regionalized and individualized manner according to the available foods and Mexican traditional food culture that may lead to a healthier dietary pattern.